21. EFFECTIVE PROPHYLACTIC ANTIBIOTICS IN SURGICAL TREATMENT OF CLAVICLE FRACTURE BY PLATE FIXATION AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2023)
Objectives: To estimate the remedial efficacity of prophylactic antibiotic rules in clavicle fracture cases experienced open reduction and plate fixation at Military Hospital 175. Subjects and methods: A descriptive retrospective study on 147 cases with closed clavicle fractures treated by open reduction and plate fixation at Military Hospital 175 from January 2020 to December 2021. Assessment of ASEPSIS score after surgery. Results: The effectiveness of the prophylactic antibiotics program enforced at the hospital with the surgical site infection rate after surgery in the group of cases using prophylactic antibiotics and the control group wasn’t statistically significant. In one hundred forty-seven cases, no case had surgical site infection at the time of follow-up examination. In both groups, 100% of patients were discharged with good wound healing according to the ASEPSIS scale. The postoperative hospital stay of the prophylactic antibiotics group was shorter than that of the control group. Profitable effectiveness is shown quite clearly between the two groups. The average cost of antibiotics for a course of surgery in the prophylactic antibiotics group was 76.43 ± 86.87 thousand Vietnam dong, nearly 1/10 of the average cost of antibiotics for a course of treatment for one case in the control group, was 754.64 ± 757.84 thousand Vietnam dong, (p < 0.05). Conclusion: Applying KSDP in surgery to treat clavicle fracture by open reduction and plate fixation is a method to improve treatment efficiency and patient safety.
Keywords: Prophylactic antibiotics, clavicle fracture, ASEPSIS.